33.
Let x=log9(p)
Thus 9x=p
1 32x=p
Since all three expressions are equal,
x=log12(q)
12x=q
2 (3.22)x=q
Also
x=log16(p+q)
x16=p+q
3 24x=p+q
p+q=p+q
1+2=3
(32)x+(3.22)x=24x
32x+(3x)(22x)=24x
Simplifying
32x + 3x = 22x
22x
the brackets are supposed to be ar
1
2
a) yes
b) yes
c) yes
d) no
e) no
f) yes
a) 1/16
b) 1
c)1
d) 216
3) 17
4)
if f(x) = | x-2 |, and f(f(x) = 8, then
| | x-2 | -2 | = 8
| x-2 | -2 = +8 or -8
| x-2 | = -6 or +10
x-2 = +6 or -6 or +10 or -10
x = 8 or -4 or 12 or -8
5)
6)
7)
a)odd
b) odd
c)